The Effect of Smoking Habits on Decreased Liver Function in Active Smokers Aged 20-50 Years old - Mike Permata Sari; Afifa Radhina; Privia Muliamarshanti (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: A study was conducted to determine the effect of smoking habits on decreased liver function in active smokers aged 20-50 years. This study was motivated by Indonesia’s high smoking prevalence and its associated liver-related health issues. The liver is an organ that plays a role in the body's metabolism. Smoking triggers the formation of free radicals, causing a decrease in liver function and inflammation. METHOD: In this study, mix method design was used with active smokers as the smoker group and the control group was respondents not active or passive smokers. Groups are categorized again based on age, ie 20-30, 31-40, and 41-50. The study population is the academic community of the Hermina Health Institute Jatinegara Campus and the community living on Kapitan III Road Tapos District, Depok City. Liver function is evaluated through enzymes SGPT, SGOT, ALP, and CRP as parameters for inflammation. To evaluate the influence of smoking habits and lifestyle factors on liver function risk, an analysis of variance (ANOVA) followed by post-hoc testing and linear regression analysis were performed. RESULT: Laboratory results showed that mean levels of ALT, AST, ALP, and CRP were higher in the smoker group compared to controls across all age categories, although most values remained within normal limits. ANOVA revealed statistically significant differences in all biomarkers (p<0.05), and post-hoc tests identified specific age-related group differences. Smokers’ habit data indicated that most smokers began smoking between the ages of 15–20 and had smoked for over five years. Lifestyle analysis showed a higher prevalence of insufficient physical activity, reduced sleep duration, and higher BMI among smokers. CLDQ scores for both groups generally reported minimal emotional disturbance and no signs of advanced liver disease. CONCLUSION: Smoking is associated with elevated liver enzymes (ALT, AST, ALP) and CRP levels, indicating subclinical hepatic and inflammatory alterations. These biochemical changes correlate with lifestyle risk factors and diminished quality of life. Early screening and lifestyle modification are recommended to prevent long-term hepatic damage among smokers.